Simulasi Steady State dan Dynamic pada Kolom De-isobutanizer dengan Penambahan Invers Decoupling pada Sistem Closedloop - Zahrotul Azizah (Journal of Research and Technology, 2021)
Degenerative Control in the Multi Input Multi Output (MIMO) system is an important topic of process control in industry. The interaction between variables in the process becomes a challenge in designing controllers for MIMO systems. Unwanted interactions cause reduced system performance which results in waste. The addition of inverse decoupling is a new strategy in reducing interactions in the process. The proposed strategy was tested on a de-isobutanizer distillation column. The results obtained were that the IAE value in the inverse decoupling added to the 2DoF IMC structure using the Mp-GM tuning method was smaller than the 2DoF IMC structure without inverse decoupling. This structure could reduce the interaction between variables in the MIMO 2×2 process.